Pengaruh Partisipasi Anggaran Dan Penekanan Anggaran Terhadap Kesenjangan Anggaran (Studi Kasus Pemerintah Daerah Kabupaten Majene) - Indra Basir; Muhammad Ihsan Ansari; Jumardi; Abdul Galib; Muh Aslam (MANDAR: Management Development and Applied Research Journal, 2023)
This study aims to find out how budget participation and budget emphasis affect budget gaps in majene district government. The population in this study was all official offices in Majene Regency, which amounted to 20 offices. The sample selection method is purposive sampling. The sample of this research amounted to 60 samples. Data analysis using multiple linear regression test analysis tools, data validity and realibility test and classical assumption test consisting of normality test, multicholinearity test, heteroskedasticity test, . Hypothesis testing is carried out by partial testing (t), simultaneous testing (f), and determination (R2 ). The results of data analysis or multiple linear regressions show that partially (t) the variables of budget participation and budget emphasis affect budget lengths, Simultaneously (f) budget participation, and budget emphasis affects jointly on budget lengths. In the adjusted column R square is 0.470 or 47%, which means budget participation and budget emphasis in explaining the budget equivalent variable of 47% while 53% is explained by other variables not described in this study.